remainder = - 1
6x² + 11x - 3 ÷ (x + 2 ) = 6x - 1 - [tex]\frac{1}{x+2}[/tex]
Answer: The required remainder is 1.
Step-by-step explanation: We are given to find the remainder when the following polynomial is divided by (x + 2) :
[tex]p(x)=6x^2+11x-3.[/tex]
Remainder Theorem : If a polynomial f(x) is divided by (x - a), then the remainder is f(a).
So, for the given polynomial p(x), the remainder will be equal to p(-2).
We have
[tex]p(-2)\\\\=6(-2)^2+11(-2)-3\\\\=24-22-3\\\\=-1.[/tex]
Thus, the required remainder is -1.